MAJELIS DZIKIR DAN KEARIFAN LOKAL : (Kajian Fenomenologis Di Desa Tambung Kec. Pademawu Kab. Pamekasan) - Rusdi Rusdi; Miftahol Arifin (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
This research aims to analyze the application of local wisdom values, such as local customs and traditions at the Asy Syarifah Dhikr and Shalawat Council. The research uses a qualitative approach which attempts to describe the behavior of subjects and events in the form of literature research and empirical research. This research uses a phenomenological study approach to reveal symptoms/phenomena that have attracted a lot of public attention related to local wisdom. The results of the research show that the Asy Syarifah Dhikr and Shalawat Council fosters religious values/religious messages, education, morals, and a sense of brotherhood/ukhuwah or social values. The religious or Islamic values ​​contained in the dhikr assembly and Asy Syarifah prayers are clearly visible, namely in the Arabic poetry and prayers of the Prophet. In the dhikr and Shalawat Asy Syarifah assembly, members are taught the ethical values ​​of relationships between young people in everyday life. Meanwhile, social and cultural values ​​are visible in this assembly, namely the members of the assembly often meet so that social interaction occurs which leads to mutual understanding and familiarizing themselves with one another.